1991
DOI: 10.1192/bjp.158.6.817
|View full text |Cite
|
Sign up to set email alerts
|

The Nature and Severity of Disabilities in Long-Stay Psychiatric In-patients in South Glamorgan

Abstract: Long-stay psychiatric in-patients in South Glamorgan were reviewed using the MRC Needs for Care assessment. The majority were middle aged or elderly and were severely disabled, with problems encompassing symptoms/behavioural difficulties, social skills, and physical health. In most, long-standing psychiatric illness was compounded by physical illness and cognitive deficits as age advanced, producing care needs that were greater than existing community services could meet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 11 publications
1
17
0
1
Order By: Relevance
“…4,11,14,18 Little is known about these institutions and their residents in Latin American countries. For this reason, the World Health Organization (WHO) is encouraging investments for assessing this information.…”
Section: Introductionmentioning
confidence: 99%
“…4,11,14,18 Little is known about these institutions and their residents in Latin American countries. For this reason, the World Health Organization (WHO) is encouraging investments for assessing this information.…”
Section: Introductionmentioning
confidence: 99%
“…The rates of recidivism in the patient with chronic mental health disability can be as high as 55% (Bruffaerts et al, 2004;Dhossche & Ghani, 1998). This transient nature coupled with known inattention to personal hygiene (Hatfield & Lefley, 1987;Pryce et al, 1991) increases the risk of exposure to nosocomial infection and transmission within a psychiatric facility. Infection control in a mental health setting is challenging, considering the health, ability, and behaviours associated with psychiatric disability (Leggett & Williams, 2000).…”
Section: Hand Hygiene Among Mental Health Workersmentioning
confidence: 99%
“…A study of 156 chronic psychiatric inpatients (Pryce et al 1991) found that 41.7% of the sample had a current problem and unmet needs relating to communication and interaction. Another study (Emerson and Enderby 1996) sought to examine the prevalence in one mental health unit of a district health authority.…”
Section: Mental Healthmentioning
confidence: 99%